Climate change: Understanding impacts on agrifood systems and evaluating policy options - Rosegrant, Mark W.; Bryan, Elizabeth; Thomas, Timothy S.; Wiebe, Keith D. (International Food Policy Research Institute, 2025)
Climate change is a major challenge of our time, with global and far-reaching effects on and from agriculture and food systems. This chapter reviews the evolution of research on climate change, food security, and food systems, reflecting on IFPRI’s major contributions to understanding and modeling climate change impacts and identifying promising policies and investments for mitigation and adaptation.